PENGEMBANGAN MATERI PEMBELAJARAN KOMIK DIGITAL KOMIK CELESTIAL OBJEK UNTUK MEMFASILITASI MINAT BACA SISWA KELAS VI SD - Nurhayatun Husna; M. Jaya Adi Putra; Jesi Alexander Alim (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article reports developmental research about digital comics on celestial objects learning material to facilitate sixth-grade elementary school students’ reading interest. The type of research was research and development (R&D) using ADDIE model, Analysis, Design, Development, Implementation, and Evaluation. The data were obtained through questionnaires. Subject of the research involved sixth-grade public elementary school students of 96 Pekanbaru. The validation results that were validated by the validator on digital comic media, which consisted of 6 assessment aspects achieved an average score of 94.37% with a very valid category. The results from limited trials obtained an average score of 93.16% with a very decent category. Above all, it can be concluded that digital comics learning material celestial objects to facilitate the sixth-grade elementary school students’ reading interest were proper to use for learning media in elementary school.